Language without rights - Wee, Lionel, 1963- (New York ; Oxford : Oxford University Press, 2011)
'Language without Rights' is a critique of the concept of language rights. Synthesizing insights from a variety of disciplines, including linguistic anthropology, sociology sociolinguistics & political philosophy, Wee demonstrates how the appeal to language rights faces a number of conceptual & practical problems.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 21, 2010).
Keywords: Language policy; Linguistic minorities